Komunikasi Organisasi Badan Komunikasi Pemuda Remaja Masjid Indonesia dalam Menanggulangi Maraknya Tindakan Kriminal - Mansyursyah Mansyursyah; Muktarruddin Muktarruddin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Percut Sei Tuan District faces quite significant problems related to crime, especially among the younger generation. The growing phenomenon of crime, such as fights between groups of teenagers, drugs, and other acts of violence, have disturbed the community and disrupted public order. Therefore, this study aims to examine how the organizational communication of the Indonesian Mosque Youth Communication Agency in overcoming the rampant criminal acts in Percut Sei Tuan District. The method used in this study is a descriptive qualitative method, with a case study approach. Data collection in this study includes observation, interviews and documentation. While the data analysis technique refers to the Miles and Huberman model which includes: data reduction, data presentation and drawing conclusions. The results of the study show that the Indonesian Mosque Youth Communication Agency has succeeded in carrying out its role as a facilitator in educating the community of Percut Sei Tuan District about preventing crime. Through various activities, such as religious studies, seminars, short Islamic boarding schools, and celebrations of Islamic holidays, the Indonesian Mosque Youth Communication Agency has succeeded in increasing public awareness about the dangers of crime and the importance of maintaining security together. In addition, the communication strategy used by the Indonesian Mosque Youth Communication Agency, including the use of social media and cooperation with religious figures and local communities. In addition, routine activities held by the Indonesian Mosque Youth Communication Agency, such as interactive religious studies and skills training, play an important role in shaping the character of the younger generation and strengthening the spiritual and social quality of the community, which in turn can reduce the potential for crime in the sub-district. Indicators of the success of the Indonesian Mosque Youth Communication Agency in overcoming the rampant criminal acts in Percut Sei Tuan District can be seen from the reduction in cases of juvenile delinquency around the mosque environment, the increase in youth participation in positive activities such as catfish farming, and the growing public awareness of the importance of the role of the mosque as a center for moral development and empowerment.